CONSEQUENCES OF SEVERE TRAUMATIC BRAIN INJURY IN CHILDREN AND THEIR TREATMENT - N.N. Zavadenko; A.I. Kemalov ("Paediatrician" Publishers LLC, 2006)
Traumatic brain injury is one of the major causes for invalidization in children. The research purpose is an integrated study of consequences of severe and moderate closed traumatic brain injury in children and evaluation of their dynamics during therapy by means of a no tropic medication - cerebrolysin (Ebewe Pharma, Austria). The total of 283 children aged from 4 to 14 years were examined in the longaterm period of severe and moderate closed traumatic brain injury, from 6 months to 4 years after injury. Their neurological status was characterized by nona specific focal symptoms along with evident motor coordination disturbances, elements of dynamic and staticoloa comotory ataxia, reduction in execution speed of serial movements. Statistically significant differences with ageamatched controls were confirmed for measures of acousticaverbal memory and sustained attention. Posttraumatic epilepsy developed in 16 (5,7%) patients with the onset of secondarily generalized seizures in 4-12 months following the injury. Effectiveness of the no tropic medication was evaluated in 60 patients aged from 7 to 12 years, who were distributed into 2 equal groups. The research has confirmed a positive effect of no tropic medication in the treatment of traumatic brain injury consequences manifested in the regression of headaches, fatigue, motor coordination disturbances along with improvements of memory, attention, intellectual performance rates, as well as EEG characteristics. Key words: traumatic brain injury, consequences, children, therapy, nootropic medications.